Self-potential tomography and multi-beam bathymetry of a deep-sea polymetallic sulfide deposit at Southwest Indian Ridge - Zhongmin Zhu; Chunhui Tao; Jinsong Shen; Andre Revil; Xianming Deng; Shili Liao; Jianping Zhou; Wenyi Wang; Zuofu Nie; Junyu Yu (PANGAEA, 2020)
Two lines of marine self-potential data were collected from Yuhuang hydrothermal field on the Southwest Indian Ridge (SWIR, Indian Ocean). A deep-towed system allowed to measure electric field data near the seafloor continuously. Although the line is approximately a straight line, we used a quadratic function to fit the ultra-short baseline (USBL) positioning data.